Global Investment Promotion Best Practices : Winning Tourism Investment - World Bank Group (Washington, DC, 2014)
Global investment promotion best practices (GIPB) assess how well national investment promotion intermediaries (IPIs) from 189 countries attract investment. The assessment is carried out by a review of IPI websites and mystery shopper inquiries that mirror the process in which foreign investors decide the location of the next projects. GIPB 2012 assessment results revealed poor performance of a staggering majority of IPIs in providing information and assistance to prospective investors in the tourism sector (investment facilitation) - a core function of IPIs worldwide. It should also be noted that less than half of the IPIs that listed tourism as a priority sector responded to the inquiry, which even then was often with incomplete information. Based on international best practices, this report recommends that IPIs adopt five key steps in order to position their agencies and locations more competitively for new tourism investment: (1) develop more strategic, focused, and relevant approaches to tourism investment promotion; (2) improve overall capacity and skills to deliver effective investment promotion with an emphasis on developing better tourism-specific knowledge in-house, especially regarding the market and the product; (3) present tourism information succinctly, using up-to-date facts, and data as well as testimonials from successful tourism companies; (4) disseminate information to investors more effectively through a mixture of existing and customized instruments (such as websites, detailed sector profiles, and tailored presentations); and (5) learn to leverage partnerships to maximize results. This report provides practical recommendations, tips, and examples aimed at helping IPIs implement the five-step approach, and it highlights actual cases from some of the best performers.